Decomposition of 14C-Malathion in three brazilian soil samples - Helene, Cecilia Gusmão; Rüegg, Elza Flores; Lord, Kenneth Alan (Pesquisa Agropecuaria Brasileira, 2014)
The degradation of 14C-malathion in soil was examined using gas chromatography and radiotracer techniques. About half of the malathion added was degraded within a day in soil from three regions of Brazil. Almost all the radiolabelled material extracted from the Red Latosol (Londrina, PR) was malathion, but metabolites were extracted from the "Sandy" cerrado soil (Planaltina, DF.) and Dark-Red Latosol (Passo Fundo. RS). The proportion of metabolites in the extracts increased until most of the malathion was degraded, after four days. Radiocarbon dioxide was liberated from all three soils at similar rates. When about half of the label had been recovered as carbon dioxide after eight weeks, the rate of evolution diminished.
Keywords: Cerrado; latosol; radiometric techniques